Evaluation of African tomato landraces (Solanum lycopersicum) based on morphological and horticultural traits - Tembe, Kenneth O.; Chemining’wa, George; Ambuko, Jane; Owino, Willis (Agriculture and Natural Resources, 2018)
Crop landraces represent a reservoir of genetic diversity; hence understanding and utilizing the genetic variation in tomato accessions are essential for improving the crop. The objective of this study was to characterize 69 tomato landraces from the World Vegetable Centre and the National Genebank of Kenya to identify desirable morphological and horticultural traits that could be used for tomato crop improvement. Field experiments were laid out in a randomized complete block design with three replicates at the University of Nairobi’s Kabete field station, Kenya, in 2014 and 2015. Principal component analysis showed that the first five components explained 78.4% of total variation among the genotypes. Traits that contributed most to variability were the presence of green shoulder, fruit size, exterior fruit color, pubescence density, flower color and fruit cross section shape. Cluster analysis grouped the accessions into two major clusters. Cluster I contained 63 accessions while cluster II had six accessions. Analysis of variance for quantitative traits indicated significant differences among the accessions for single leaf area, soil plant analysis development, days to 50% flowering, days to maturity, the number of fruits per plant, fruit width, fruit length and fruit weight per plant. Fruit weight per plant ranged from 565.0 g to 2759.0 g per plant and showed a positive significant correlation with fruit length (r = 0.28) and fruit width (r = 0.30). The study showed the existence of wide genetic diversity among the tomato accessions thus providing scope for future genetic improvement of the crop.